2011
DOI: 10.1890/09-1999.1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and remote sensing of leaf mass per area (LMA) in humid tropical forests

Abstract: Leaf mass per area (LMA) is a trait of central importance to plant physiology and ecosystem function, but LMA patterns in the upper canopies of humid tropical forests have proved elusive due to tall species and high diversity. We collected top-of-canopy leaf samples from 2873 individuals in 57 sites spread across the Neotropics, Australasia, and Caribbean and Pacific Islands to quantify environmental and taxonomic drivers of LMA variation, and to advance remote-sensing measures of LMA. We uncovered strong taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
109
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 45 publications
(44 reference statements)
15
109
1
Order By: Relevance
“…Some of most accurately predicted traits have no absorption features in the visible-to-near-infrared, but were instead estimated indirectly via constellation effects. LMA is consistently among the more accurately predicted traits using spectroscopy (Asner and Martin, 2008;Serbin et al, 2014;Chavana-Bryant et al, 2016), but is measured indirectly via its close coupling with water content and structural traits of leaves (Asner et al, 2011b). Silicon (Si) concentrations were well predicted by field spectroscopy, as recently reported by Smis et al (2014).…”
Section: Measuring Interspecific Variation In Leaf Traitssupporting
confidence: 60%
“…Some of most accurately predicted traits have no absorption features in the visible-to-near-infrared, but were instead estimated indirectly via constellation effects. LMA is consistently among the more accurately predicted traits using spectroscopy (Asner and Martin, 2008;Serbin et al, 2014;Chavana-Bryant et al, 2016), but is measured indirectly via its close coupling with water content and structural traits of leaves (Asner et al, 2011b). Silicon (Si) concentrations were well predicted by field spectroscopy, as recently reported by Smis et al (2014).…”
Section: Measuring Interspecific Variation In Leaf Traitssupporting
confidence: 60%
“…For example, species distribution in tropical rain forests may show a weak relationship to environmental gradients at local and regional scales due to stable climatic conditions. Remote sensing of vegetation patterns in such areas hence requires approaches based on the biochemistry of the target species using advanced sensor technologies (e.g., [7]). (2) Indirect relationships as used in this study are complex and hardly transferable.…”
Section: Theoretical Limitations Of the Approachmentioning
confidence: 99%
“…In particular at global and regional scales, where ground-based mapping is inefficient, remote sensing may be a practical alternative approach for vegetation mapping. Environmental conditions, such as climate, also affect the biophysical and biochemical properties of species and hence influence their spectral signal [4,7]. Environmental conditions, especially temperature and precipitation, are further major determinants of species distribution at macroscales [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…High Fidelity Imaging Spectroscopy (HiFIS) is an emerging technology that utilizes high spectral resolution remotely sensed reflectance data to estimate foliar or canopy characteristics [5,6]. Utilizing reflectance data from the visible to shortwave infrared (400-2500 nm), HiFIS has been used to successfully predict foliar traits from tropical trees at the leaf scale [7][8][9][10]. In addition, it has recently been demonstrated that, in the tropics, community-scale canopy functional traits can be estimated at the hectare level using airborne HiFIS [11,12].…”
Section: Introductionmentioning
confidence: 99%